(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Using annual time series data on the number of children (ages 0 – 14) newly infected with HIV in Lesotho from 1990 – 2018, the study predicts the annual number of children who will be newly infected with HIV over the period 2019 – 2030. The research applies the Box-Jenkins ARIMA methodology. The diagnostic ADF tests show that, X, the series under consideration is an I (0) variable. Based on the AIC, the study presents the ARIMA (3, 0, 1) model as the optimal model. The residual correlogram reveals that the presented model is indeed stable. The results of the study indicate that the number of new pediatric HIV infections in Lesotho is likely to decline, over the period 2019 – 2030, from approximately 1258 to almost 123 new infections by 2030. This is a “green light” towards the achievement of an AIDS free society in Lesotho. The study encourages the government of Lesotho to continue intensifying PMTCT services in the country to ensure victory in the fight against pediatric HIV, at least 10 years from now